PM.85 Diagnosing PE in Maternity Patients. An Audit of Radiological Investigations and Clinical Interpretation. (26th April 2013) - Newell, T; Taylor, K; Kelly, R; Morgan, D
Abstract : VTE is an important cause of maternal mortality but signs and symptoms are unreliable. Ionising radiation has hazards for the fetus and mother. Current American Thoracic Society guidelines recommend VQ scans in preference to CTPA if chest x-ray and lower limb Doppler are negative but clinical suspicion remains. VQ scans are not diagnostic, results are given as a probability of PE, i.e. none, low, intermediate or high which can be difficult for the clinician to interpret. We undertook an audit to compare practise with guidelines and assess clinical interpretation of VQ scans. Results were compared with CTPA. All maternity patients, between 8 weeks gestation and 6 weeks post-partum, undergoing VQ or CTPA were identified from a radiology database. Clinical information was obtained from notes and computerised records. Data was analysed with excel and 2 × 2 tables. 78 maternity patients were identified, 5 had PE identified on CTPA. Chest x-ray was performed in 92% patients and lower limb Doppler in 68% (audit standard 100%). VQ scans were performed in 59% women and CTPA in 56%. 60% patients with low/intermediate and intermediate VQ scans underwent CTPA and 2 (33%) were found to have PE. In the 12 patients who underwent both CTPA and VQ scanning, the sensitivity of VQ was 33% and specificity was 60%. Clinicians need to be aware of the high probability of PE in patients with intermediate results, and in many cases even a low probability result should prompt consideration of CTPA.